Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae) - Najer, Tomas; Gustafsson, Daniel R.; Sychra, Oldrich (Zootaxa, 2016)
Two new species of the louse genus Philopteroides Mey, 2004 are described and illustrated from two host species of painted berrypeckers, endemic to New Guinea: Philopteroides sinancorellus n. sp. ex Oreocharis arfaki (Meyer, 1875) (tit berrypecker), and Philopteroides gigas n. sp. ex Paramythia montium De Vis, 1892 (crested berrypecker). Both louse species belong to the beckeri species-group based on their short, broad preantennal areas, and shallow median indentations of the hyaline margin. The description of these two new species brings the total number of Philopteroides species to 15. An amended key to the beckeri species-group is included.